Demand preferences for health management services in a population of older adults with visual impairment in China: a conjoint analysis - Li, Shuqin; Wang, Ai-ping (BMC geriatrics, 2022)
Visual impairment (VI) seriously affects the quality of life of the older adults. It is important to formulate appropriate health management strategies for the older adults with VI to help delay the disease development and progression, and improve life quality. The aim of this study was to understand the demand preference for health management services of the older adults with VI, and to provide a reference for the development of future health management strategies in this population. The conjoint analysis method was used to analyze demand preferences for health management services of the older adults with VI. 11 keywords were extracted after literature analyzed, 6 keywords were selected as the attributes of health management strategy after expert discussion and the level of each attribute was determined. Then 18 representative virtual health management strategies were formed by combination of different attribute levels through orthogonal design, and older adults with VI were asked to score. A total of 334 older adults with VI who attended the ophthalmology department of the First Affiliated Hospital of China Medical University and the Fourth People's Hospital of Shenyang from February 27, 2021 to June 30, 2021were enrolled in this study by stratified sampling. Of the 334 included people, 80 had grade 1 VI, 80 had grade 2 VI, 84 had grade 3 VI, and 90 had grade 4 VI. The relative importance of health management services ranked by older adults with VI was continuing care (24.033%), visual aid application (19.61%), health education (16.241%), preventive healthcare (15.667%), safety management (12.757%), and rehabilitation training (11.392%). The utility values of each level of continuing care, safety management and preventive healthcare were positive, whereas the utility values of each level of visual aid application, health education and rehabilitation training were negative. The relative importance and utility values of health management services were different for the older adults with different grades of VI. From the whole group, the older adults with VI have a higher preference for continuing care and a lower preference for rehabilitation training. The preference of the older adults with different grades of VI is different, so medical workers can formulate corresponding health management strategies according to their different demand preferences, and carry out hierarchical health management. Services that they preferred should be satisfied as much as possible in the health management strategy, while the reasons for the services with lower preference can be explored and make targeted improvement to meet the demand preferences of them.